Lipid sac area as a proxy for individual lipid content of arctic calanoid copepods - Vogedes, Daniel Ludwig; Varpe, Øystein; Søreide, Janne; Graeve, M; Berge, Jørgen; Falk-Petersen, Stig (Journal of Plankton Research, 2010)
We present an accurate, fast, simple and non-destructive photographic method to estimate wax ester and lipid content in single individuals of the calanoid copepod genus Calanus and test this method against gas-chromatographic lipid measurements.